Tahapan Legislasi Perda pada Pendidikan Inklusif Oleh DPRD kota Pariaman - Rana Adiza Putri (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study discusses the stages of legislating a Regional Regulation (Perda) related to inclusive education conducted by the Regional People's Representative Council (DPRD) of Pariaman City. Inclusive education is a strategic effort to achieve educational equity for all levels of society, including persons with disabilities. In this context, the role of the DPRD as a regional legislative body is crucial in formulating policies that are responsive to the needs of inclusivity. Using a qualitative approach with documentation studies and in-depth interview methods, this study identifies and analyzes each stage in the legislative process, from planning, drafting, and deliberation to the ratification of the regulation. The findings show that although the legislative process has followed formal procedures, challenges remain, particularly in terms of public participation and inter-agency coordination. This research recommends strengthening the capacity of legislators and optimizing community participation to produce more inclusive and implementable regulations.